M- GOVERNANCE – AN EFFECTIVE WAY TO UTILIZING E-GOVERNANCE IN INDIA - Dr. Jaya Iyer & Dr. Sindhu Singh (International Journal of Research Science and Management, 2017)
Information and Communication Technology (ICT) is the most indispensible fastest growing sector in the world. The government can use ICT to provide better services to the citizen as well as in the government departments. The government can interact with the citizen through a service called e-governance portal which is based on internet. E-Governance usage is increased in urban area, but has failed in the rural area due to the lack of proper infrastructure and illiteracy. The government can combine internet and mobile technologies to implement government services more effectively. Mobile devices and its subscription are comparatively higher than the Internet usage in India. The high penetration of mobile devices and the high speed broad band technologies like UMTS (Universal Mobile Telecommunications System), wireless networks offer various opportunities in the government administration to provide better service to the citizen. E-Governance has already improved to speed-up of public utility services, but mobile services with their 24X7 –functionality can facilitate mobile governance to establish a direct contact with the citizens. This paper discusses the various initiatives of e-governance and m-governance in India